A study to determine the level of cord blood albumin in predicting neonatal jaundice - Hirevenkanagoudar, Usha; M., Pranam G.; Chetty, Sanjeev (International Journal of Contemporary Pediatrics, 2020)
Background: Most unconjugated bilirubin formed by the fetus is cleared by the placenta into the maternal circulation. Albumin constitutes 70 - 75% of Plasma oncotic pressure. Another important function of albumin is its antioxidant property. Bilirubin binds to albumin in an equimolar ratio. Free bilirubin is anticipated when the molar bilirubin- to- albumin (B: A) ratio is >0.8 Objective of the study was to predict the proportion of newborn requiring intervention for NH (phototherapy or exchange transfusion) based on cord serum albumin level at birth. Methods: The present prospective study was conducted at Navodaya Medical College, Raichur from October 2018 to November 2019. A total of 180 babies which were born during the study period were included in the study. INCLUSION CRITERIA• Term babies both genders• Mode of delivery (normal and C-section)• Birth weight ≥2.5kg.• APGAR ≥7/10 at 1 min. Cord Serum Albumin level was estimated at birth. Total Serum Bilirubin (TSB) estimation was done at 72-96 hours of age. All the babies were followed up daily for first 4 postnatal days and babies were daily assessed for NH and its severity. Results: In our study nearly 54.4% of them had Cord Serum Albumin levels of less than 2.8 gm/dl, 27.3% of them had albumin levels of 2.9 to 3.3 gm/dl, 18.3% of them had Serum Albumin of 3.4 gm/dl. Out of 180 study subjects, 13.9% of them required phototherapy to treat neonatal hyper bilirubinemia and 2.8% of the study subjects required exchange transfusion. Conclusions: From the present study, cord serum albumin level of ≤2.8g/dl has a correlation with incidence of significant hyperbilirubinemia in term newborns. So, this ≤2.8g/dl of cord serum albumin level can be used as risk indicator to predict the development of significant hyperbilirubinemia.